Mobilization of the Empty Box Volunteer Movement to Face the Single Candidate in the 2020 Pilkada of Humbang Hasundutan Regency, North Sumatra Province - Harahap, Riky Ovaliansyah; Kosandi, Meidi (Universitas Medan Area, 2024)
This article aims to find out about the mobilization of the empty box movement facing a single candidate in the Humbang Hasundutan Regional Election, North Sumatra Province in 2020. The problem focuses on the emergence of the empty box volunteer movement in the Humbang Hasundutan Regional Election in 2020. In order to approach this problem, theoretical references from Edwards and McCarthy are used, namely Resource Mobilization theory. Data was collected through in-depth interviews and triangulation as well as literature review and analyzed qualitatively. This study concludes that the emergence of Empty Box Volunteers in Humbang Hasundutan, which was initiated by the Humbang Hasundutan Democracy Care Forum, was caused by the disappointment of elements of society with political parties which were considered to be harming democracy because they limited the choice of regional head candidates.